Intramolecular Cyclization of Aryl Propargyl Ethers: A Straightforward and Convenient Approach to Benzofuran Derivatives - Hosseinian, Akram; Babazadeh, Mirzaagha; Edjlali, Ladan; Rahmani, Zahra; Vessally, Esmail (Current Organic Synthesis, 2018)
Background: Benzofurans are very important structural motifs found in a great number of natural products and biologically active compounds. Many commercially available drugs, including citalopram, dronedarone, saprisartan, darifenacin, and galantamine are derived from benzofuran core entities. Due to the diversity of benzofuran derivatives in the therapeutic response profile, developing novel and truly efficient methods for their synthesis from low-cost and easily accessible starting materials in one-step has been the subject of number of papers in recent years. Objective: Propargylic ethers are one of the most specific class of heteroatom-containing alkynes showing a large application as intermediates in organic synthesis. These compounds were successfully transformed into various organic compounds, including chromenes, carbazoles, cyclopentanones, 1, 2-dihydropyridines, α, β- unsaturated ketones, alcohols, allenes and many more. Synthesis of benzofurans via intramolecular cyclization of aryl propargyl ethers has become one of the most popular applications of theses versatile compounds. In this review we will highlight the recent discoveries and advances in this interesting research arena. Method: The review is divided into two major sections. The first will discuss cyclization of ortho-halo aryl propargylic ethers, while the second focuses exclusively on cyclization of ortho-unsubstituted aryl propargyl ethers. It is should be mentioned that special emphasis is placed on the mechanistic aspects of these reactions. Conclusion: Synthesis of benzofuran derivatives via intramolecular cyclization of corresponding aryl propargyl ethers have witnessed rapid and comprehensive development in recent years. The main advantages of this synthetic strategy include the use of simple, inexpensive, non-toxic, and readily accessible starting materials, and its pot, atom, and step economy.
Keywords: 2; 3-dihydrobenzofurans